135k views
2 votes
Solve w = t(11 + r) for t.

User Mike Ross
by
5.0k points

2 Answers

5 votes

Answer:

t = w/(r + 11)

Explanation:

Solve for t:

w = t (r + 11)

w = (r + 11) t is equivalent to (r + 11) t = w:

t (r + 11) = w

Divide both sides by r + 11:

Answer: t = w/(r + 11)

User Marycatherine
by
5.8k points
1 vote

Answer:

t = w/(11+r)

Explanation:

To solve for t, we need to divide anything that t is multiplied to to get it on the other side of the equal sign.

w = t(11+r)

w/(11+r) = t

User Gracy
by
5.0k points